2013
DOI: 10.1519/jsc.0b013e3182815770
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Functional and Static Evaluation Tools Among Adolescent Athletes

Abstract: This study aimed to compare functional movement screen (FMS [TM]) scores and Beighton and Horan joint mobility index (BHJMI) scores among pubescence in adolescent athletes. Sixty-six adolescents between the ages of 8 and 14 voluntarily participated in this study. The participants performed the tests of the BHJMI, the tasks of the FMS (TM), and the clearing tests of the FMS (TM). The composite scores of the FMS (TM) and the BHJMI were scored objectively by the same researcher. The subjects were separated into p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 23 publications
4
25
0
1
Order By: Relevance
“…Indeed, actual movement skills are one of the few modifiable risk factors for the prevention of poor health outcomes (Bremer & Cairney, 2016), and therefore promoting movement skill proficiency is integral to a holistic view of development . Similar to the low levels of FMS proficiency observed in the present study, overall functional movement skill execution is also low amongst participants, which is consistent with other previously published functional movement adolescent literature (Paszkewicz, McCarty, & van Lunen, 2013;Portas, Parkin, Roberts, & Batterham, 2016). Overall, the mean composite FMS™ raw score for this study was 14.05 (out of a possible 21), which is similar to the mean values reported by Abraham et al, (2015) on 1005 mixed-gender adolescents in India.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, actual movement skills are one of the few modifiable risk factors for the prevention of poor health outcomes (Bremer & Cairney, 2016), and therefore promoting movement skill proficiency is integral to a holistic view of development . Similar to the low levels of FMS proficiency observed in the present study, overall functional movement skill execution is also low amongst participants, which is consistent with other previously published functional movement adolescent literature (Paszkewicz, McCarty, & van Lunen, 2013;Portas, Parkin, Roberts, & Batterham, 2016). Overall, the mean composite FMS™ raw score for this study was 14.05 (out of a possible 21), which is similar to the mean values reported by Abraham et al, (2015) on 1005 mixed-gender adolescents in India.…”
Section: Discussionsupporting
confidence: 92%
“…43 However, recent studies of youth in the southeastern US revealed that females perform better on the FMS TM when evaluating composite scores (male = 14.67, female = 15.16; male = 12.62; female = 14.40). 3,44 Therefore, this study provides another reference for sex comparison using the composite FMS TM score in young participants, specifically the high school population.…”
Section: Discussionmentioning
confidence: 99%
“…Across the FMS TM literature there has been conflicting evidence regarding sex differences in youth and the composite FMS TM score. 3,43,44 The normative data for youth (ages 10-17) from India demonstrate that males outperform females regarding the composite FMS TM score (male = 14.93, female = 14.17). 43 However, recent studies of youth in the southeastern US revealed that females perform better on the FMS TM when evaluating composite scores (male = 14.67, female = 15.16; male = 12.62; female = 14.40).…”
Section: Discussionmentioning
confidence: 99%
“…The Functional Movement Screen (FMS) [8]), is one such measure which is predictive of injury risk [9] and has been shown to improve following online video-based compared to fully supervised resistance exercise in adolescent basketball athletes [10]. Recent work by Paszkewicz et al [11] has also reported that the FMS can discriminate between levels of pubescence and detect alterations during the pubertal growth cycle in children and adolescents aged 8-14 years old. The FMS comprises seven movement tests that employ a variety of positions and movements closely related to normal growth and development [12].…”
Section: Introductionmentioning
confidence: 99%